'Chained to my work'? Strategies to manage temporal and physical boundaries among self‐employed teleworkers. (19th December 2012) - Mustafa, Mona; Gold, Michael
Abstract : It is accepted that teleworkers generally manage the balance between their home and working lives by establishing temporal and physical boundaries between the two along a continuum of role integration–segmentation. What is less understood is the nature of the relationship between temporal and physical boundaries, and how teleworkers control constituent elements of physical boundaries to secure their preferred location along the continuum. Based on 20 interviews with self‐employed teleworkers, this article examines the ways in which successful control of time depends largely on the successful control of space. It investigates in particular how teleworkers attempt to control space by breaking it down into constituent elements involving equipment, activities and ambiance.